Bagaimana Workplace Ostracism Mempengaruhi Turnover Intention yang Dimediasi oleh Job Performace dan Organizational Virtuousness Serta Authentic Leadership Sebagai Moderasi - Unik Dwi Lestari; Muvinna Adnal Haq; Tantri Yanuar Rahmat Syah; Rojuaniah; Egi Supriatna (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study examines the impact of workplace ostracism on employee turnover intention in manufacturing companies in Bekasi Regency, as well as the moderating roles of authentic leadership and organizational virtuousness in this relationship. Utilizing a quantitative approach with an online questionnaire employing a Likert scale, the research involved 202 respondents selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling-Partial Least Square (SEM-PLS) to assess the relationships among variables and their validity. The findings indicate that workplace ostracism significantly affects employee turnover intention. However, perceptions of organizational virtuousness and authentic leadership did not positively moderate this relationship. Additionally, workplace ostracism negatively impacts job performance, while lower job performance is negatively related to turnover intention. These results underscore the importance of fostering an inclusive and supportive work environment to mitigate ostracism, enhance job performance, and increase employee retention.